The consequences of the syndrome of the pre-menstrual tension in the woman’s life - Muramatsu, Clarice H.; Vieira, Olga Cristina Serafim; Simões, Cirilo César; Katayama, Daniela Aparecida; Nakagawa, Flávia Hiroko (Revista da Escola de Enfermagem da USP, 2001)
This study has as objective to identify the possible consequences of the Syndrome of the Pré-menstrual Tension in the woman's life. Through the questionnaire, we identified disturb related to physical and emotional discomfort and as consequences the alterations in the relationships involving son, husband / boyfriend and family, as well as in the work atmosphere.